2009
DOI: 10.1002/ps.1729
|View full text |Cite
|
Sign up to set email alerts
|

Potential for microbial diuron mineralisation in a small wine‐growing watershed: from treated plots to lotic receiver hydrosystem

Abstract: This study provides strong suggestive evidence for high diuron biodegradation potential throughout its course, from the pollution source to the final receiving hydrosystem, and suggests that, after microbial adaptation, grass strips may represent an effective environmental tool for mineralisation and attenuation of intercepted pesticides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 35 publications
5
36
0
Order By: Relevance
“…In addition, and interestingly, the mineralization kinetics obtained with upstream sediments in this study (Fig. 3) were quite similar to those obtained, following the same protocol, with sediments collected in June 2007 (Pesce et al, 2009) and February 2008(Pesce et al, 2010b at the same sampling site. This temporal stability over seasons and years further strengthens the reproducibility of the observations reported here, and justifies the use of the upstream sediments as reference in the present study.…”
Section: Can Upstream Sediments Be Taken As Reference Samples?supporting
confidence: 85%
See 3 more Smart Citations
“…In addition, and interestingly, the mineralization kinetics obtained with upstream sediments in this study (Fig. 3) were quite similar to those obtained, following the same protocol, with sediments collected in June 2007 (Pesce et al, 2009) and February 2008(Pesce et al, 2010b at the same sampling site. This temporal stability over seasons and years further strengthens the reproducibility of the observations reported here, and justifies the use of the upstream sediments as reference in the present study.…”
Section: Can Upstream Sediments Be Taken As Reference Samples?supporting
confidence: 85%
“…6D). In summer 2007, a similar gradual increase in diuron mineralization potential along the Morcille river was reported, with higher diuron-mineralizing ability observed in the downstream section of the river for both periphytic biofilm and sediment communities (Pesce et al, 2009). It is noteworthy that studies on the potential of natural freshwater sediments to degrade synthetic pesticides are scarce ( Kalsch et al, 1998, Larsen et al, 2000, Toräng et al, 2003and Trinh et al, 2012, but there is now convincing evidence that the capacity of microbial sediment communities to biodegrade these contaminants can increase after an in situ longterm pre-exposure to these compounds ( Toräng et al, 2003 andTrinh et al, 2012).…”
Section: Can Upstream Sediments Be Taken As Reference Samples?supporting
confidence: 63%
See 2 more Smart Citations
“…For example, Guash and Sabater (1998) showed that the differences in algal diversity linked to the light history of a biofilm can lead to differing responses to the presence of herbicides. Seasonal factors or spatial variability can also result in communities displaying differing diversity and differing susceptibilities to contaminants (Dorigo et al, 2009), including their ability to degrade pesticides (Pesce et al, 2009b). In a long-term laboratory experiment to test the effect of atrazine after grazing Muñoz et al (2001) demonstrated that grazers increased the toxic effect of atrazine on river biofilms.…”
Section: Interactions Between Environmental Selective Pressures and Hmentioning
confidence: 99%